Study Of e-Service Availability And Awareness Among Higher Education Students In Libya - Zainab A. Elmabruk Abdelsadeq
The Libyan academic Institutions faces a multitude of challenges regarding the , iii. ibility of e-services to quality technological infrastructure promoting electronic conununication. Moreover Libyan students suffer from limited awareness to modern academic trends and instructors themselves are deficient in their experience when gyred to other countries. Hence, the main objectives of this study were to evaluate lability of c-services and to determine the awareness level for c-services among ! idents in Libyan universities This research study identified the impact of the : '. affability of e- services and the students' awareness on the implementation of eerý ices in higher education in Libyan universities. In order to achieve the research two objectives have been accomplished. The data were collected from three ýý111c1st universities in different areas in Libya: 1 Tripoli university in Tripoli ( the iI city) which located in the west of Libya, 2- Benghazi university in Benghazi which located in the middle of Libya and 3- Omar AL-Mukhtar university (ALHeada university )eastern of Libya. After collecting the data it was analyzed to identify ýi explore the impact of the awareness and the availability on the adoption of c- "I"'ices in selected universities. The findings of the research have been discussed, laally tests to (Ieter111111C the Impact of these factors on the Implementation of ein the three cases. This study is the first study that has identified these critical )r : Illcctino the implementation of' e- Services in higher education in LibVan 111mnsT. he finding of this research is that the awareness Of, students and of infrastructure were very important factor affecting c Services adoption success inlplenlcntation in institute of'higher education in Libya.